2008
DOI: 10.2298/apt0839171p
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of acid protease from Penicillium roqueforti in aqueous two-phase system polyethylene glicol/phosphate

Abstract: The partitioning of acid protease produced by submerged fermentation of Penicillium roqueforti in the aqueous two-phase system polyethylene glycol/sodium phosphate was studied. In the system with 15% polyethylene glycol 4000/25% NaH2PO4 favourable partition coefficient and the top phase yield were obtained, 2.651 and 56.51%, respectively. The purification of acid protease from crude enzyme was optimized by optimizing separation factor. Completely randomized factorial design was applied and the system 15.54% PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…As discussed, our protease recovery results are similar to or even higher than those reported by other authors, where PEG/salt ATPS were also used to purify different enzymes (38,(40)(41)(42)(43)(44)(45)(46). Furthermore, although the PF obtained in our study were generally lower than other systems reported in the literature, it is important to note that this parameter is directly related with to the initial protease/total protein ratio.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As discussed, our protease recovery results are similar to or even higher than those reported by other authors, where PEG/salt ATPS were also used to purify different enzymes (38,(40)(41)(42)(43)(44)(45)(46). Furthermore, although the PF obtained in our study were generally lower than other systems reported in the literature, it is important to note that this parameter is directly related with to the initial protease/total protein ratio.…”
Section: Discussionsupporting
confidence: 89%
“…A large number of studies that analyzed the recovery of proteases in PEG/phosphate ATPS have been performed (42)(43)(44)(45)(46), in which the PF and Y values for the partitioning of the proteases were similar to the values reported by our group. However, the concentration of phosphate used in these systems was between 15-50 wt %, which leads to environmental concerns, avoiding a large industrial application.…”
Section: Atps Is Presented In Supplementary Informationsupporting
confidence: 62%